We extend our memories in the sun (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
From a theater workshop developed at the Female Presidium of Florianópolis, the play We Extend Our Memories in the Sun. On a rainy day, a child is faced with the disappearance of his grandparents. We are invited to join the child in a journey, which is both a search and a series of encounters. The fable is interspersed with memories of the actresses. A memory made of water can be transformed into a letter, an invitation to throw in the sun, to stretch out on the patio, on public soil that is (or should be) the world.
Keywords: Dramaturgy; Female prison; Theater Pedagogy